Transtracheal ultrasonography versus endtidal capnography in rapid confirmation of endotracheal tube placement - Shruthi Rioniz; Nischala Dixit; Preethi Rioniz; Thomas T Vellapally; Nayanthara Joachim; Siddhanth Suresh (Asian Journal of Medical Sciences, 2025)
Background: Prompt confirmation of proper endotracheal (ET) tube placement after intubation is imperative to averting life-threatening consequences. Waveform capnography, although the gold standard method, poses some limitations while transtracheal ultrasonography (USG) is a reliable real-time technique that has shown much promise. Existing literature on the faster method has yielded conflicting results. Aims and Objectives: This study aims to determine the mean time taken to confirm the correct placement of the ET tube using both transtracheal USG and end-tidal capnography. A comparative assessment of the faster method will supplement patient care by helping anesthesiologists avoid accidental esophageal/endobronchial intubation and the associated morbidity. Materials and Methods: Consenting adult patients posted for elective surgeries under general anesthesia were recruited over a period of 18 months. The time taken for confirmation of correct tube placement by both transtracheal USG and capnographic end-tidal carbon dioxide tracing was recorded. A paired samples t-test was used to compare the means (±standard deviation). Results: The study included 112 patients aged 40.1±12 years of whom 59 (52.6%) were females. The mean time taken to confirm tube placement by USG and capnography was 35.8±9.8 s and 67.4±13.7 s, respectively, with a mean time difference of 31.6±7.8 s which was found to be statistically significant (P<0.001). Conclusion: Transtracheal USG is the faster method to confirm the proper placement of an ET tube during intubation when compared to waveform capnography. USG is also beneficial in detecting and avoiding accidental esophageal intubations.